Answer:
x=-1 , y=-2
Step-by-step explanation:
Replace y in the first equation with x-1.
So, we have -4x+3(x-1)=-2
Multiply brackets with 3: -4x+3x-3=-2
-4x+3x=-2+3 (-3 becomes +3 after it changes sides)
-x=1 /*(-1)
x=-1
After we have x we include it in y=x-1
y=-1-1
y=-2
7x, because 12x − 8x + 3 = 4x + 3 = 7x
12x − 5, because 12x − (8x − 3) = 12x − 5
x, because 12x − 8x + 3 = 12x − 11x = x
Answer:
A. 3 + 4x, because (12x − 8x) + 3 = 4x + 3 = 3 + 4x.
Step-by-step explanation:
12x − 8x + 3 is equal to 3 + 4x.